Rheumatic Complete Atrioventricular Block: A Case Report - Saousan Serbout; Hamza Choukrallah; Leila Azzouzi; Abdenasser Drighil; Rachida Habbal (Publisher: Shahid Beheshti University of Medical Sciences)
Acute rheumatic fever is a well-known disease that is still widely observed in developing countries, including our country Morocco. It is known that the majority of patients diagnosed with acute rheumatic fever display abnormalities of the conduction system; However, there are only a few case reports that describe severe impairment in the electrical conduction system. We describe a 21-year-old man who was diagnosed with acute rheumatic fever with complete atrioventricular block. In our patient, the diagnosis of acute rheumatic fever was established. 24-hour electrocardiography showed a paroxistic complete atrioventricular block. Penicillin prophylaxis was made, and salicylate treatment in an anti-inflammatory dose was initiated. The electrocardiographic abnormalities of the patient disappeared. Although rare, this diagnosis should be considered in patients with complete heart block, particularly when it is associated with other features of acute rheumatic fever. Conduction disorders associated with acute rheumatic fever often resolve following appropriate treatment without the need for permanent pacemaker placement.